Analisis Strategi Pemasaran PT Indra Langgeng Jaya - Ustraliw Nur Kurnia Esa; Abdurahman Faris Indriya Himawan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The company's growth is currently experiencing an increase in the fields of services, industry, and trade. Competition within the company cannot be avoided by all companies that move in accordance with the aim of continuing to live and develop. Basically, marketing strategy provides direction in relation to variables such as market segmentation, identification of target markets, positioning of marketing mix elements, and marketing mix costs. PT. Indra Langgeng Jaya is a private company engaged in loading and unloading services. The company is fully managed by professional experts in the service sector. PT. Indra Langgeng Jaya is based in Gresik, East Java. This study uses a qualitative descriptive research method with data collection from observations and interviews with informants from the management of PT. Indra Langgeng Jaya. In the past 4 years, the company has experienced a decline in loading and unloading activities, because many competitors have cooperated with PT. Wilmar Nabati Indonesia. Company management must have a marketing strategy to increase loading and unloading activities by promoting employees and social media websites supported by good facilities and services for customers.